2022
DOI: 10.3389/fnut.2022.1020855
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative, cytoprotective and whitening activities of fragrant pear fruits at different growth stages

Abstract: Pear is one of the most popular fruits in the world. With the fruit ripening, a series of physiological changes have taken place in fragrant pear, but up to now, the research on the metabolism and biological activity of phenolic compounds in different growth stages of fragrant pear is still lacking. In this study, four kinds of Xinjiang pears were selected as research objects, and the changes of phenolic content, antioxidant capacity, cell protection and whitening activity during fruit development were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Jiang et al [26] showed that the phenolic content and antioxidant capacity of four pear cultivars had a decreasing trend throughout the developmental stages. The study was performed without partitioning into fruit components (peel or flesh); our results for flesh are within the range indicated by the authors.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al [26] showed that the phenolic content and antioxidant capacity of four pear cultivars had a decreasing trend throughout the developmental stages. The study was performed without partitioning into fruit components (peel or flesh); our results for flesh are within the range indicated by the authors.…”
Section: Discussionmentioning
confidence: 99%
“…Some pear varieties are characterized by a gritty texture, primarily due to the presence of stone cells [ 4 ]. These stone cells have thick cell membranes and limited internal space, which can contribute to the slow ripening of pears [ 5 ], in addition to higher oxidative stress in fruits [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of ROS, which can result from normal metabolic processes or environmental stresses, can lead to cellular damage, and have a detrimental impact on fruit development, quality, and post-harvest storability [ 9 ]. The application of antioxidants or antioxidant-enhancing compounds via sprays is hypothesized to reduce oxidative stress in pear trees, thereby enhancing both fruit yield and quality [ 5 , 6 ]. Numerous studies have explored the effects of foliar antioxidant treatments on various fruit crops, including pears.…”
Section: Introductionmentioning
confidence: 99%